Evaluation of rabies awareness and the population dynamics of free-roaming and owned dogs in Herat city, Afghanistan - Nasiry, Zabihullah (2022)
The existent uncontrolled dog population in Herat city has a negatively influenced public health leading to socioeconomic, and animal welfare problems. The objectives of the study were to characterize demographics and estimate the population size of both owned and free-roaming dogs, to assess dog bites cases, and knowledge, attitude, and practices of the community towards rabies and to estimate the post-exposure treatment costs associated with dog bites in Herat city, Afghanistan. These aims were achieved by a Door to door household questionnaire survey, Random-digit dial telephone questionnaire survey and Photographic sight-re-sight method. A total of 928 Free-roaming dogs (FRD) were identified through 3172 sightings, and total of free-roaming population were estimated 1821 (95% Confidence Interval (CI): 1565-2077), which led to an estimate of 10 dogs/km2 with the human: free-roaming dog ratio of 315:1. The male to female ratio was 2.85:1. Majority of them were healthy and had ideal body condition score. Approximately 24.6% of the households owned one or more dogs. The total owned dogs were estimated to be 20,642 (95% CI= 22,764 – 18,630) dogs with density of 113 dogs/km2. The owned dog: human ratio was 1: 27.79 (0.035 dog per person). The male to female ratio of owned dog was 5.1:1. Almost 76.7% of households kept dogs confined and only 19% of dogs were vaccinated against rabies. Approximately 4,845 dog bite cases had been referred to health centres of Herat city from December 22, 2019 to March 20, 2021, and seven fatality cases due to rabies have been recorded. Out of 581 dog bite victims interviewed, majority of them (90.8%) were bitten by free-roaming dogs. This study revealed that the extremities were the most (90.3%) inflicted parts. Most dog bite victims were predominantly male and children. More than half (58%) of bite victims took measures to treat the bite wound before seeking health centre and 88.8% of them were visited health centres immediately. Majority of dog bite victims (92.3%) received rabies Post-exposure prophylaxis (PEP) and 67% completed the PEP course. Besides that, the majority of the respondents (83.5%) had previously heard about rabies, 77.5% believed that rabies is a dangerous and lethal disease and more than half (61.6%) of also believed that rabies is a preventable disease. There was high level (97.3%) of awareness that dog bite is the main cause of rabies. The total direct medical and indirect costs due to dog bites were estimated to be 9.658992 million Afghani (120,737 USD) and 2.88 million Afghani (36044 USD) per year respectively. The total societal costs (direct medical costs plus indirect costs) were estimated to be 12.538992 million Afghani (156,781 USD) per year. Although the dog density is considered low, the dog bites rate and economic costs are considerable, so it still warrants caution since a proportion of the population is not well-versed about dogs and their importance of them in the transmission of zoonotic diseases like rabies. The information generated by this research can help to identify considerations for the design and implementation of dogs and rabies control programs.